The importance of being earnest: Trial registration and full disclosure in publishing in health psychology - Hagger, Martin (Routledge, 2013)
There have been recent calls for increased disclosure of important methodological, statistical, and data components of research reported in publication outlets. This is particularly important to ensure that the research can be replicated (e.g., intervention manuals and protocols) and data can be subjected to secondary analyses. This is extremely relevant given the proliferation of systematic reviews and meta-analyses to synthesize research findings and it is important that such syntheses are not biased due to lack of data availability. Currently, most journals operate a voluntary code in terms of disclosure and there is inconsistency in the application of guidelines for the clear reporting of research findings such as CONSORT or MARS. This means that researchers’ ethical obligations to make their findings readily available to others are not subject to strict control. Clearer guidelines need to be put in place by journal editors in order to ensure that authors fulfill these obligations without compromising ownership over data and protocols. Similarly, many journals are now making formal registration of trials by an approved regulatory body (e.g., WHO international clinical trials registry, Australian and New Zealand Clinical Trials) obligatory. This is a useful as registry permits formal logging and sharing of information about current trials including detail on the focus, design, and ethical aspects. Currently this is voluntary in most health psychology journals, but with Open Access journals leading the way, this is likely to be revised. This will be a positive step, along with the disclosure of research data, toward better transparency in research.